Fabrication of Quad Bike - Kalra, Dr. Kapil (IJRDO - Journal of Mechanical And Civil Engineering, 2018)
ATV stands for all-terrain vehicle also known as Quad-Bike. The purpose of fabricating a Quad-Bike was to manufacture an off-road vehicle that could help in transportation in hilly areas, farming field and as a reliable experience for a weekend enthusiast. The machine used in the fabrication of the chassis was lathe, grinding machine, cutting machine and the welding was done by MIG, TIG and Arc. And the software used as per the designing purpose was Catia, SolidWorks and Fusion 360. Material used was AISI 1020 steel and the Result was able to successfully modify a 2-wheeler bike (Yamaha RX-100) into a 4-wheeler ATV. The objective of designing a single-passenger off-road race vehicle with high safety and low production costs seems to be accomplished. The design was first conceptualized based on personal experiences and intuition.